TINJAUAN ASPEK HUKUMTERHADAP POLA PENGGUNAAN LAHAN DI DAERAH ALIRAN SUNGAI CILIWUNG BAGIAN TENGAH Studi Kasus : Kecamatan Cimanggis - Yuslim, Silia; Mangunsong, Nur Intan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
The development of urban and sub urban of Jakarta has influenced Ciliwung riverbank, which finally damaged environment. Lacal government ‘Kabupaten Bogor’has made RUTRW (Rencana Umum Tata Ruang Wilayah), general plan for regionaluse space to control the development and to avoid more damaged environment.However, there are many divergences occur in the land use. Observation to currentarea of the river in the Ciliwung in the middle area was hopping can give somesuggestion to government for more aware and keep environment away from moredamaged.